Effects Of Formal Authority And Experience On Third-Party Roles, Outcomes, And Perceptions Of Fairness - Karambayya, Rekha; Brett, Jeanne M.; Lytle, Anne L. (Academy of Management Journal, 1992)
Using a simulated organizational dispute, we contrasted the behavior of intervening third parties who had formal authority over the disputants to that of third parties who had no authority over them and examined the effect on third-party behavior of actual supervisory experience. The study also tested the relationships among third-party behavior, the outcome of the dispute and disputants' perceptions of fairness. Subjects were M.B.A. candidates and executive program participants; 99 percent had full-time work experience and 30 percent had more than five years of supervisory experience. Both the manipulated role and actual supervisory experience affected third-party behavior, which in turn affected outcome and fairness judgments.